Answer:
C) x = 3, y = -6
Explanation:
![\textsf{Equation 1}:x-2y=15](https://img.qammunity.org/2023/formulas/mathematics/high-school/q0xktaabrnuac4v2njoau7f3a0dvu2eu3r.png)
![\textsf{Equation 2}:2x+4y=-18](https://img.qammunity.org/2023/formulas/mathematics/high-school/s2l4s4i7kn1z6lf8zzcgszdczjcc241u78.png)
Rewrite Equation 1 to make x the subject:
![\implies x=15+2y](https://img.qammunity.org/2023/formulas/mathematics/high-school/16lfqhxqwms16dghtw4ou77ghpphulwud9.png)
Substitute into Equation 2 and solve for y:
![\implies 2(15+2y)+4y=-18](https://img.qammunity.org/2023/formulas/mathematics/high-school/xhr76j0yww5fncey0jsfo76ixihaps54ub.png)
![\implies 30+4y+4y=-18](https://img.qammunity.org/2023/formulas/mathematics/high-school/1hzm7ex7b239m6xqkgps5ph1eegxad5r7d.png)
![\implies 8y=-48](https://img.qammunity.org/2023/formulas/mathematics/high-school/n3otj3a1cucui0lb1x5ke4sowb8qch1kym.png)
![\implies y=-6](https://img.qammunity.org/2023/formulas/mathematics/high-school/lzmysxvwhhvry1sfhlpyoj2voce63be0d9.png)
Substitute found value of y into Equation 1 and solve for x:
![\implies x-2(-6)=15](https://img.qammunity.org/2023/formulas/mathematics/high-school/hc9ind191jvh6eezzgscf5o2mob23ov8jv.png)
![\implies x+12=15](https://img.qammunity.org/2023/formulas/mathematics/high-school/kpy5ohlgpe2xjh4nx68ww1nl27yie6h0hn.png)
![\implies x=3](https://img.qammunity.org/2023/formulas/mathematics/high-school/mzf4ih6guqait6h2fqn9pc6o8r041andur.png)
Therefore, the solution to the system of equations is:
x = 3, y = -6